Studies on the whey proteins of cows` milk in induced lactation - Sadananda Talukdar (Department of Dairy Science, College of Veterinary and Animal Sciences, 1985)
A comparative study on the milk proteins in general and the whey proteins in particular was conducted between cows of first lactation and inferitile heifers brought into lactation by hormonal treatment. It was intended to study the differences, if any, between the two sets of cows in respect of the milk proteins and the possible secretory process involved therein . An exhaustive review of literature has been presented on the levels of various components of whey proteins and other related aspects. The methods of analysis of various components of milk have been detailed. The cows used in the study were crossbred ones, randomly selected from the University Livestock Farm, Mannuthy and maintained under similar farm conditions. The experimental group of animals, the heifers, were given estrogen (0.1 mg/kg body weight) and progesterone (0.25 mg/kg body weight) together in a single injection daily for 7 days consecutively. Gradual development of the udder during the course of treatment was noticed. Between the termination of the treatment and first milking, the development was more conspicuous. Regular milking, twice in a day, was started from the 21st day after the first injection. Secretion was initially colostral, and gradually within a period of 5 days, it resembled normal milk in appearance. The minimum yield from one animal in a day was 200 ml whereas the maximum reached was 4, 500 ml. From the 16th day of first milking, chemical analysis was started with in the case of experimental group. Animals in the control group began with the 3rd month of their lactation when the sample collection was started for analysis. Milk samples from both the groups were collected every 6th day and thus 6 samples from each animal were used for analysis. Both chemical analysis and electrophoresis were used to study the milk components. Estimation of nitrogen was done by the kjeldahl method. Average contents (in percentage) of albumin, globulin, total whey protein and other whey proteins were 0.383, 0.1786, 0.64 and 0.10 respectively in the milk of normal lactation; the values in the induced lactation being 0.603, 0.284, 1.045 and 0.158 respectively. Out of the total nitrogen in milk, the total whey nitrogen and the non protein nitrogen were 26.526 and 6.376 per cent respectively, in normal lactation, the values were 31.524 and 5.432 per cent respectively. Average total protein, casein and crude protein contents in normal milk were 2.97, 2.33 and 3.17 per cent respectively. But in induced milk, the values were 3.79, 2.773 and 4.007 per cent respectively. The ratio of whey protein :casein was 22:78 in normal lactation whereas in induced lactation it was 27;73. The contribution of whey protein to the higher total protein content of induced milk is more than that of casein. Differences between the whey components between the two groups were noticed. On statistical analysis, albumin, globulin, non – protein nitrogen and the other whey proteins together (whey proteins excluding albumin plus globulin) did not have significant difference between the two groups. So also was the casein. There was, however, significant difference between the two groups in respect of total whey nitrogen, total whey protein and total protein. Individual differences were highly significant in respect of albumin, globulin, total whey protein, total protein and crude protein. The last one had highly significant difference between the groups also. Globulin, non – protein nitrogen and other whey proteins, on the other hand, did not indicate any significant difference neither between groups or between individuals. The whey protein was subjected to electrophoretic separation in Acrylamide gel system with Borate buffer. In this attempt, it could be fractionated into six different bands in each case. But the mode of fractionation between groups in particular was found different from each other. A general trend for an increase in the protein content was thus seen in the milk of induced lactation that was mostly brought about by whey proteins. This may be a reflection of the secretory pattern involved with the normal and the induced lactation. Further investigations in detail may elucidate this in future.